Practice patterns in longitudinal lupus care provision: patient and physician perspectives. (December 2017) - Kugasia, A; Sehgal, N; Dollear, M; Sequeira, W; Block, J A; Jolly, M
Background/purpose: To plan a quality improvement project, we need to understand the practice patterns of physicians. We undertook an online survey of systemic lupus erythematosus (SLE) patients and physicians providing care to SLE patients to determine the patterns of medical care provided to SLE patients. Materials and methods: Two self-report surveys were developed. A 12-item survey for the patients and a 13-item survey for physicians enquired about longitudinal care for SLE. Surveys were administered online to physicians providing care to SLE patients, and to patients who self-identified as having SLE, through the Lupus Society of Illinois. Patient and physician data were analyzed for physician practice patterns for SLE care, using chi square tests and t tests. A P value of 0.05 or less was considered significant on two-tailed tests. Results: A total of 283 patients completed the survey. Mean (SD) age and disease duration of patients were 45.9 (13.2) and 12.7 (9.7) years. Half of the participants were being seen at 3–4-month intervals. More than 70% of patients reported being tested for antinuclear antibody (ANA), and 20–30% anti-ENA antibody and Sjögren's (SSA/SSB) antibodies, respectively, at each follow-up visit. Eighty-six rheumatologists completed the surveys. Mean (SD) age was 55 (12) years and 56% were men. More than half (54%) provided care only in a private practice setting. More than 80% of physicians reported seeing their SLE patients at 3–4-month interval. Only 2% reported performing ANA tests at each visit, while 4–5% performed anti-ENA and anti-SSA/SSB antibody tests at each visit for their SLE patients. More than 75% of physicians in private practice also ordered sedimentation rate at each visit for their SLE patients. Conclusions: Unnecessary laboratory investigations may be being ordered routinely for patients at every visit. These results indicate a need for physician education on indications and utility of some of the laboratory tests such as ANA.